Computational logic in multi-agent systems 13th International Workshop, CLIMA XIII, Montpellier, France, August 27-28, 2012. Proceedings - Fisher, Michael (Lecture notes in computer science, 2012)
This book constitutes the proceedings of the 13th International Workshop on Computational Logic in Multi-Agent Systems, CLIMA XIII, held in Montpellier, France, in August 2012. The 11 regular papers were carefully reviewed and selected from 27 submissions and presented with three invited papers. The purpose of the CLIMA workshops is to provide a forum for discussing techniques, based on computational logic, for representing, programming and reasoning about agents and multi-agent systems in a formal way.